Analysis Of The Influence Of Digital Brand Perception And E-Wom On Repurchase Intention Of Internet Protocol Television Service Product - Kuspriyono, Taat; Silvia Ekasari; Arifai Ilyas; Donny Dharmawan; Musran Munizu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to determine whether brand image and unfavorable electronic word-of-mouth factors have an impact on repurchase intentions. The study's population consists of social media users in a few Indonesian cities. With a sample size of 100 respondents, researchers employed a non-probability sampling method with a purposive sampling strategy. This study use questionnaires and literature reviews as data collection methods. Researchers employed quantitative techniques in this study. The path analysis method was applied by researchers. Based on the findings, it was determined that the negative electronic word-of-mouth variable had a direct impact on the brand image variable. The purchasing choice variable is directly impacted by the unfavorable electronic word-of-mouth variable. The repurchase intention variable is directly impacted by the brand image variable. Negative brand perception and electronic word-of-mouth have an impact on the repurchase intention variable. Via the brand image variable, the negative electronic word-of-mouth variable indirectly affects the repurchase intention variable. The aforementioned points provide an explanation for how brand image influences repurchase intentions when it comes to electronic word-of-mouth. It is intended that these findings would help the business sustain and improve electronic word-of-mouth on social media in the future.